بیسویں صدی میں اردو سیرت نگاری کے مناہج و اسالیب - سید عزیزالرحمٰن (FIKR-O NAZAR فکر ونظر, 2012)
The contemporary sciences under a secularist- materialist world view have led the humankind to serious consequences by denying the spiritual and religious dimensions of knowledge. Consequently, the humankind's material comfort is portrayed as an alternate to true happiness of soul and body. This problem is acute in social sciences, because it does not influence only an individual in its personal capacity but it also has an impact on the whole society. This has effected the economic, social and political environment which needs a paradigm shift in the light of divine knowledege. This paper attempts to highlight the impact of modern epistemology on 20th century Sirah literature and suggests how these developments in social sciences can be utilized in Sirah writings without disturbing it's divine nature.